Economic Preneur's Innovative Strategy in Facing the Economic Crisis - Shino, Yamato; Utami, Fransisca; Sukmaningsih, Sekar (Pandawan Sejahtera Indonesia, 2024)
The global economic crisis has placed significant pressure on Economic Preneurs, compelling them to adopt innovative strategies to sustain their businesses amidst challenges. This research delves into the myriad of innovative strategies employed by Economic Preneurs to effectively navigate economic downturns. Utilizing a qualitative research methodology, the study conducts in-depth interviews with fifty Economic Preneurs spanning various industries. The findings shed light on the effectiveness of several strategies, including digital transformation, diversification of service offerings, and a heightened emphasis on customer value optimization. Through these strategies, Economic Preneurs strive to adapt to changing market conditions and customer preferences, ensuring the resilience and viability of their enterprises. Ultimately, it is observed that Economic Preneurs who demonstrate agility and innovation in response to economic challenges are more likely to not only weather financial adversities but also thrive and expand their enterprises. This study contributes to the existing body of literature by offering empirical evidence on resilience tactics utilized during economic crises and provides practical insights for business leaders and policymakers. These insights can inform the creation of conducive environments that foster entrepreneurial innovation and promote economic sustainability in the face of adversity.